Bioequivalence Study of two Formulations Containing 30 mg of Aripiprazole in Healthy Human Volunteers - MANDAL, U.; GHOSH, A.; PAL, T.K.; CHATTARAJ, T.K. (Asian Journal of Chemistry, 2010)
Aripiprazole is a new anti-psychotic drug used for the management of Schizophrenia, a brain disorder. A simple and sensitive reversed phase high performance liquid chromatography coupled with UV detector set at 215 nm has been used to determine plasma concentration of aripiprazole in healthy male human volunteers. The method has been validated over a linear range of 20-400 ng/mL from plasma. The minimum quantifiable concentration (LOQ) obtained was 20 ng mL-1 (% CV < 10 %). The pharmacokinetic parameters (Cmax, AUC0-t, AUC0-∞) of this drug have been evaluated by the above method to compare the single oral dose (30 mg) bioavailability of aripiprazole with the reference formulation in 12 healthy male volunteers of two way, two periods cross over randomized study. Adverse effects leading to postural dizziness and blood pressure lowering have been observed in some of the volunteers. Although ECG reports confirm the non-significant physiological change. The pharmacokinetic parameters were Cmax = 118.82 ± 20.76 ng mL-1 at tmax = 3.96 ± 0.69 h, AUC0-t = 4962.67 ± 1189.54 ng h mL-1, AUC0-∞ = 7266.75 ± 2146.78 ng h mL-1, Kel = 0.0138 ± 0.0025 h-1 and t½ = 51.69 ± 9.80 h.